Implementasi Desain Pembelajaran Sejarah Mode Bauran (Blended Learning) Berbasis Digital - Nafi’ah, Ulfatun; Musdad, Akhmad Arif (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2024)
This research aims to determine the implementation of digital-based blended learning history design in SMA/SMK in Malang City. This study used a descriptive qualitative method. Data collection techniques were carried out using observation, documentation, interviews, and open questionnaires. The research subjects were the PPG Pre-Service History Practicing Teachers at the State University of Malang, Phase II, who carried out practical field experiences at SMAN 1, SMAN 10, SMKN 4, and SMKN 6, Malang City in 2023. To check the validity of the data, data triangulation was carried out. The data analysis carried out was narrative-qualitative. Data analysis in this research includes data reduction, data presentation, and conclusion. The research results show that the blended learning mode that has been implemented can increase student learning outcomes from an average of 61.33 to 89.5. Students' psychomotor learning outcomes increase with product evaluation through virtual exhibition activities. The implementation of mixed-mode history learning in vocational and senior high schools runs effectively by teachers conducting classroom observations and adjusting students' learning needs. Apart from that, history teachers apply various varied learning models, namely project-based learning (PJBL) and problem-based learning (PBL). Evaluation is carried out to improve students' cognitive, affective, and psychomotor abilities. History learning activities are carried out with a learning process that integrates high-level thinking (HOTS). Learning also uses various digital media including Canva, video, Padlet s.id, and educational games, capable of producing critical, creative, and innovative historical learning. The mixed implementation mode used has challenges for history teachers including having to provide clear instructions for the learning process; for vocational school students, history subjects are not productive learning, so teachers supervise learning so that students focus on historical material; Vocational school teachers provide differentiated assignment options for determining the type of product produced.